Disentangling the effects of management and climate change on habitat suitability for saproxylic species in boreal forests - Ekman, Ellinoora; Triviño, María; Blattert, Clemens; Mazziotta, Adriano; Potterf, Maria; Eyvindson, Kyle (Springer Nature, 2024)
Forest degradation induced by intensive forest management and temperature increase by climate change are resulting in biodiversity decline in boreal forests. Intensive forest management and high-end climate emission scenarios can further reduce the amount and diversity of deadwood, the limiting factor for habitats for saproxylic species in European boreal forests. The magnitude of their combined effects and how changes in forest management can affect deadwood diversity under a range of climate change scenarios are poorly understood. We used forest growth simulations to evaluate how forest management and climate change will individually and jointly affect habitats of red-listed saproxylic species in Finland. We simulated seven forest management regimes and three climate scenarios (reference, RCP4.5 and RCP8.5) over 100 years. Management regimes included set aside, continuous cover forestry, business-as-usual (BAU) and four modifications of BAU. Habitat suitability was assessed using a species-specific habitat suitability index, including 21 fungal and invertebrate species groups. “Winner” and “loser” species were identified based on the modelled impacts of forest management and climate change on their habitat suitability. We found that forest management had a major impact on habitat suitability of saproxylic species compared to climate change. Habitat suitability index varied by over 250% among management regimes, while overall change in habitat suitability index caused by climate change was on average only 2%. More species groups were identified as winners than losers from impacts of climate change (52%–95% were winners, depending on the climate change scenario and management regime). The largest increase in habitat suitability index was achieved under set aside (254%) and the climate scenario RCP8.5 (> 2%), while continuous cover forestry was the most suitable regime to increase habitat suitability of saproxylic species (up to + 11%) across all climate change scenarios. Our results show that close-to-nature management regimes (e.g., continuous cover forestry and set aside) can increase the habitat suitability of many saproxylic boreal species more than the basic business-as-usual regime. This suggests that biodiversity loss of many saproxylic species in boreal forests can be mitigated through improved forest management practices, even as climate change progresses.
Keywords: Biodiversity; Simulations; Finland; Forest planning; Habitat suitability; Deadwood